Development of Video-Based Learning Media on the Fuel Systems Subject to Improve Student Learning Outcomes - Sigit Purnomo; M. Gilang Arka Pratama; Alfat Khaharsyah; Muhammad Hakiki; Radinal Fadli; Kukuh Wahyudin Pratama (VANOS Journal of Mechanical Engineering Education, 2025)
Development of Video-Based Learning Media on Fuel System Subjects to Improve Learning Outcomes of SMK Muhammadiyah 1 Moyudan Students. Thesis. Vocational Education Study Program in Mechanical Engineering. Faculty of Teacher Training and Education, Sarjanawiyata Tamansiswa University Yogyakarta, 2024. This research aims to: 1. Develop appropriate video-based learning media for students to improve learning outcomes. 2. Test the feasibility of video-based learning media on fuel system subjects for SMK Muhammadiyah Moyudan students. 3. Improve students’ learning outcomes in the subjects taught.This research is a research and development (R&D) study using the ADDIE development model: Analyze, Design, Development, Implementation, and Evaluation. The development media is in the form of instructional videos. The data analysis technique uses descriptive quantitative. The research results show that: 1) This research produces EFI Fuel System instructional videos. 2) The EFI Fuel System instructional video is very feasible to use based on the validation results of material experts 1 and 2 with an average score of 82% and the media expert validation score of 91%. 3) Student responses show a very good category for use with a score of 87%. The development of the use of instructional video media was tested during the pretest with an average score of 53% and posttest 87%. The improvement in learning outcomes measured using the N-Gain formula obtained 0.3≤0.57≤0.7, which can be categorized as moderate, so the EFI Fuel System video-based learning media product is feasible to use for learning media.